Anthocyanin and proanthocyanidin contents, antioxidant activity, and in situ degradability of black and red rice grains - Hosoda, Kenji (Asian-Australasian journal of animal sciences, 2018)
OBJECTIVE: An experiment was conducted to assess the antioxidant contents and activities of colored rice grains and to evaluate their nutritive characteristics in terms of chemical composition and in situ ruminal degradation